The Relationship Between Perceived Stress Level and Consumption of Fast Foods Among Female Students of Shahrekord University of Medical Sciences - Zahra Karimi; Elahe Tavassoli; Akbar Babaei Heydarabadi (Shahrekord University of Medical Sciences, 2019)
Background and aims: Nowadays, with the advancement of science and technology, lifestyle has changed and fast foods are being commonly consumed. Due to their special circumstances, university students are susceptible to stress, anxiety, and bad nutritional patterns and, because of the consumption of high amounts of fat and salt and physical inactivity, are at increased risk of overweight and obesity. Therefore, the present research was conducted to study the relationship between the consumption of fast foods and perceived stress level among female students of Shahrekord University of Medical Sciences. Methods: The present research was a descriptive-analytical study conducted on female students of different faculties and majors in Shahrekord University of Medical Sciences in the academic year 2016-2017. From the study population, 152 students were selected as the samples using random cluster sampling method. Data were collected using a demographic information questionnaire (age, major, parents' education level, education level, and place of residence), a standard 14-item scale for the measurement of perceived stress level, and a checklist to record the frequency of fast foods consumption in university and home or dormitory (daily, weekly, and monthly). Data analysis was conducted using descriptive and analytical tests (chi-squared, independent t test, and Spearman's and Pearson's correlation coefficients) in SPSS 18. Participation in the study was voluntary. Results: Results showed 45.4% of participants aged 18-20, 16.4% of whom were studying in public health, and 85.8% were BSc students. The mean scores of perceived stress and fast foods consumption were 51.36±13.52 and 12.42±5.42, respectively. There was a significant relationship between age and perceived stress (P=0.000), and between mother's education level and perceived stress (P=0.011). There was no significant relationship between the mean score of perceived stress and fast foods consumption in participants (P=0.072) Conclusion: Considering the level of perceived stress and fast foods consumption in university students, it is necessary to apply effective patterns and theories of health education and promotion and also to direct attention to interpersonal and environmental factors to reduce stress and encourage healthy eating habits.